Determination of Macro- and Microelements in the Inflorescences of Banana Tree Using ICP OES: Evaluation of the Daily Recommendations of Intake for Humans - Rafaela Henriques Rosa; Melina Ribeiro Fernandes; Elaine Silva de Pádua Melo; Daniela Granja Arakaki; Nayara Vieira de Lima; Luana Carolina Santos Leite; Paulo Renato Espindola; Igor Domingos de Souza; Valdir Aragão do Nascimento; Paula Fabiana Saldanha Tschinkel; Fabiane La Flor Ziegler Sanches; Valter Aragão do Nascimento (The Scientific World Journal)
The inflorescence of Musa paradisiaca, known as “banana heart” is a structure that includes flowers and bracts of banana, commonly used as food source worldwide. The aims of this study were (1) to determine the mineral components of Musa paradisiaca and (2) to compare the obtained results with previously reported data of Recommendation Dietary Allowances (RDAs) and edible plant permissible limits set by FAO/WHO. The samples were digested using microwave-assisted equipment, while elemental contents were determined by inductively coupled plasma optical emission spectroscopy (ICP OES). Metal (Mg, Ca, Cr, Ni, Cu, Fe, and Zn) and nonmetal (S and P) contents were detected. According to RDA, the inflorescences could be excellent sources of Mg, P, Cr, Cu, Zn, and Fe for females, males, and pregnant women, all age 31–50 y, as well as children (4–8 y). Bracts are good source of Zn for male and pregnant women and good source of Fe for children. All the samples contained considerable amounts of Mg, Ca, P, Ni, Cu, Zn, and Fe, which were quite low to induce deleterious effects (UL). FAO/WHO limits for edible plants have not yet been established for S, P, Mg, and Ca, but Ni and Zn are below of those limit values. However, Cr and Cu concentrations are higher than the values established for edible plants and may pose a threat to human health. Farmers should be encouraged by government agencies, not only for sustainability of production but also to ensure the storage and trade of banana tree inflorescence.